DESIGN OF LINE SIDE âNEW YOGYAKARTA INTERNATIONAL AIRPORT (NYIA) â AIRPORT DRAINAGE SYSTEM IN TEMON DISTRICT, KULON PROGO, SPECIAL REGION OF YOGYAKARTA - Rimayanti, Neneng
The construction of the New Yogyakarta International Airport (NYIA) Kulon Progo airport aims to increase the capacity of transportation facilities in Yogyakarta. In an airport construction, especially in the land side airport, a drainage system is needed to avoid inundation and flooding which can infrastructure damage caused by standing water. Land side drainage system planning is intended to plan drainage schemes based on the existing master plan, planning the dimensions of the channel and its operation and maintenance activities. The drainage network layout is divided into 2 parts, that are the southern part of the JJLS and the northern part of the JJLS. The disposal plan is planned to be disposed of at four points, namely the Bogowonto River, Serang River, West Carik River and East Carik River. In calculating the drainage load discharge when the 10-year return is calculated using the rational method where the intensity of rain is calculated using the mononobe method and the time of concentration is calculated by the SNI method of road drainage consisting of land time plus channel time. Channel dimensions is calculated by the manning formula with a concrete base material and in accordance with the discharge plan of the channel. The vary dimensions is gotten from the calculation of the manning formula. The watershed flood discharge is calculated by ITB-1 method. Based on the results of the hydrograph superposition calculation, the peak discharge period of 25 return bogowonto rivers is 659,2 m3/s and the Serang river 595,1 m3/s, then the hydrograph discharge is modeled using the HEC-RAS software where this modeling aims to determine the river flood water level, so that from the flood face the planned channel elevation can be planned. The operation and maintenance is planned to be carried out on the drainage channels, and culverts .